Impacto del uso de las bicicletas como movilidad alternativa en la contaminación ambiental en la ciudad de Cuenca - Arias Argudo, Iván Mauricio (2023)
This technical project was Carrie out with the objective of analyzing the impact of the bicycle as an alternative mobility against environmental pollution, analyzing data on pollutant emissions in previous studies and applying it in different parishes according to the mobility matrix of the people of Cuenca.